Designing a novel and versatile multi-layered nanofibrous structure loaded with MTX and 5-FU for the targeted delivery of anticancer drugs. (September 2020) - Poursharifi, Nazanin; Semnani, Dariush; Soltani, Parham; Amanpour, Saeid
Abstract: In this study, multi-layered nanofiber systems consisting of polycaprolactone/chitosan (PCL/CS) polymers loaded with anticancer drugs, methotrexate (MTX) and 5-fluorouracil (5-FU), were designed and produced. The surface morphology of drug-free and drug-loaded samples was investigated by field-emission scanning electron microscopy (FESEM). Fourier transform infrared spectrometry (FTIR) was employed to study the chemical structure of polymers and drugs. The drug release test in neutral and acidic medium (pH 7.4 and pH 4.4) was carried out, and the released drug concentration was measured using UV-spectrophotometry. Moreover, the mechanical properties of single- and multi-layered samples were also studied. The FESEM images indicated the production of uniform and bead-free fibers. FTIR tests confirmed the presence of the drugs in the polymer mixture. The results revealed higher degradation and weight loss percentage in samples with higher CS content due to the hydrophilic nature of CS. Evaluating the drug release behavior of MTX and 5-FU for 624 h revealed that seven-layered structures have prolonged drug release profile and lower burst release rate. The comparison of the release profile of MTX and 5-FU in neutral and acidic environments showed that the rate and amount of release increase with decreasing the pH value. Also, results indicated that the drug release of nanofibers followed Fickian diffusion mechanism and Higuchi model kinetic. Highlights: A novel seven-layered structure loaded with two anti-cancer drugs was studied. Drug release behavior of 5-FU and MTX was evaluated at pH values of 7.4 and 4.4 Seven-layered structures provide prolonged drug release and a minimum burst release. The rate and amount of release increase with decreasing the pH value. The drug release followed Fickian diffusion mechanism and Higuchi model kinetic.